Shinto: the way home - Kasulis, Thomas P. (Dimensions of Asian spirituality, 2004)
Entering through the torii -- Everyday connectedness -- Ancient Shinto (prehistory-794) : the trailblazers -- From Nara to Norinaga (794-1801) : the pathfinders -- All roads lead to Tokyo (1801-2002) : the highway engineers -- The way home.